Niger improvement : Current status and future strategies: NIGER IMPROVEMENT : CURRENT STATUS AND FUTURE STRATEGIES - A K PANDAY; S SHARMA; R BISEN; S JAIN; M MALVIYA; A R G RANGANATHA (Journal of Oilseeds Research, 2014)
The present research efforts of breeding are reviewed in relation to the potential, considering the niger cultivation by resource poor farmers. The history of domestication and the diversity in the plant genetic resources is critically analysed for the formulation of crop improvement strategies with the emphasis on enhancing the average low yield levels in India and in the African subcontinent. The utilization of primary gene pool and the potential uses of wild species are included. Niger improvement is analysed considering population improvement, development of superior inbreds and future strategies for hybrid development. Further biotechnology, mutation and resistance breeding for biotic and abiotic stresses are considered for the production of agronomic types with wider adaptation. Niger being a cross pollinated crop, where seed quality is a serious concern, maintenance breeding and nucleus seed production is covered in detail, since 30-50 per cent productivity improvement can be realised, easily through the intervention of quality seed supply. The production and protection technologies are reviewed for improvement in niger productivity. The potential areas for future line of research are indicated for productivity improvement in niger.